Effect of different treatment protocols on in vitro fertilisation/intracytoplasmic sperm injection (IVF/ICSI) outcomes in adenomyosis women: a systematic review and meta-analysis - Wenting Wang; Li Ge; Linlin Cui; Jiayi Zhou; Yexing Li; Xueqing Zhao; Xiaojing Chen; Zhongyuan Li; Pengbo Ge (BMJ Open)
Objectives Pregnancy outcomes of different ovarian stimulation protocols for in vitro fertilisation/intracytoplasmic sperm injection (IVF/ICSI) in patients with adenomyosis are not explicit. This meta-analysis aimed to systematically evaluate the effects of different IVF/ICSI protocols on pregnancy outcomes.Design Meta-analysis.Data sources PubMed, Web of Science and Cochrane library were searched up to October 2023.Eligibility criteria Comparative studies on IVF/ICSI outcomes in the adenomyosis population were eligible. Studies on preimplantation genetic testing, reviews, case reports and animal experiments were excluded.Data extraction and synthesis Valid information was extracted by two independent authors according to a standard data format. All analyses were conducted using Review Manager (RevMan, V.5.3).Results Compared with the non-adenomyosis population, adenomyosis was responsible for a 26% reduction in clinical pregnancy rate (CPR; 42.47% vs 55.89%, OR: 0.74, 95% CI: 0.66 to 0.82, p<0.00001), a 35% reduction in live birth rate (LBR; 30.72% vs 47.77%, OR: 0.65, 95% CI: 0.58 to 0.73, p<0.00001) and a 1.9-fold increase in miscarriage rate (MR; 27.82% vs 13.9%, OR: 1.90, 95% CI: 1.56 to 2.31, p<0.00001). Subgroup analysis suggested that, in fresh embryo transfer (ET) cycles, the CPR (34.4% vs 58.25%) in the long/short/antagonist protocol group was poorer than that in the ultralong protocol group. In frozen ET (FET) cycles, there were no statistical differences in CPR ((GnRHa+FET) AM(adenomyosis) vs non-AM: 51.32% vs 43.48%, p=0.31; (non-GnRHa+FET) AM vs non-AM: 50.25% vs 60.10%, p=0.82), MR ((GnRHa+FET) AM vs non-AM:12.82% vs 12.50%, p=0.97; (non-GnRHa+FET) AM vs non-AM: 30.5% vs 15.54%, p=0.15) and LBR ((GnRHa+FET) AM vs non-AM:44.74% vs 36.96%, p=0.31; (non-GnRHa+FET) AM vs non-AM: 34.42% vs 50.25%, p=0.28). The MR in the adenomyosis group was high in the fresh ET and FET cycles.Conclusions FET might be a better choice for women with adenomyosis, especially those pretreated with GnRHa. In fresh ET cycles, pregnancy outcomes of the long/short/antagonist protocols were poorer than those of the ultralong protocol.Trial registration number CRD42022340743.